Topical cyclosporine a (0.05%) treatment in dry eye patients: a comparison study of Sjogren’s syndrome versus non-Sjogren’s syndrome - Cubuk, Mehmet Ozgur; Ucgul, Ahmet Yucel; Ozgur, Armagan; Ozulken, Kemal; Yuksel, Erdem (Springer Science and Business Media LLC, 2021)
To evaluate the clinical effect of topical cyclosporine A (CsA) (0.05%) on dry eye patients with Sjogren's syndrome (SS) and non-Sjogren's syndrome (NSS).This retrospective comparative study includes the dry eye (DE) patients who were treated with topical CsA. DE patients were divided into two groups as follows: DE with Sjogren's syndrome (DE-SS) and DE with Non-Sjogren's syndrome (DE-NSS). Dry eye parameters were recorded at baseline and each visit.Schirmer's test 1 scores were 2.7 ± 0.5 mm at baseline and 3.5 ± 0.7 mm at 12th month in DE-SS, 2.9 ± 0.7 mm at baseline and 9.5 ± 0.7 mm in DE-NSS groups at 12th month. Mean ST score was higher in DE-NSS group than DE-SS group at sixth and 12th months of the treatment (both p = 0.001). Tear break-up time score showed a significant improvement in DE-NSS group, and it was lower in DE-NSS group than DE-SS group group at sixth and 12th months of the treatment (p = 0.044 and 0.027, respectively). Mean OSDI score was lower in DE-NSS group than DE-SS group at sixth and 12th months of the treatment (p = 0.030 and 0.032, respectively).Topical CsA seems to be more effective in the treatment of the DE-NSS.
Keywords: Non-Sjogren’s Syndrome; Sjogren’s Yndrome; Dry Eye; Dry eye; Sjogren's Syndrome; Sjogren's syndrome; Tears; Cyclosporine; Humans; Dry Eye Syndromes; Non-sjogren's syndrome; Retrospective Studies; 2. Zero hunger; 3. Good health